The role and mechanism of long non-coding RNA H19 in stem cell osteogenic differentiation - Liang Wang; Lei Qi (BMC, 2021)
Abstract Background In recent years, H19, as one of the most well-known long non-coding RNA, has been reported to play important roles in many biological and physiological processes. H19 has been identified to regulate the osteogenic differentiation of various stem cells in many studies. However, the detailed role and regulation mechanism of H19 was not consistent in the reported studies. Main body of the manuscript In this review article we summarized the effect and mechanism of lncRNA H19 on osteogenic differentiation of various stem cells reported in the published literatures. The role and mechanism of H19, H19 expression changes, effect of H19 on cell proliferation in osteogenic differentiation were respectively reviewed. Conclusions An increasing number of studies have provided evidence that H19 play its role in the regulation of stem cell osteogenic differentiation by different mechanisms. Most of the studies favored the positive regulatory effect of H19 through lncRNA-miRNA pathway. The function and underlying mechanisms by which H19 contributes to osteogenic differentiation require further investigation.